(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: Dengue is a growing public health problem globally including Bangladesh. This study is carried out to find out the seroprevalence of dengue fever in Chittagong. Methods: About 1181 serum samples were tested from suspected dengue patients for IgM and IgG antibodies by immunochromatographic methods. Results: Among them, 533 (45.13%) were seropositive. Among the seropositive cases 213 (39.96%) were IgM positive, 227 (42.59%) were IgG positive and 93 (17.45%) were both IgM and IgG positive. Conclusions: A high percentage of dengue positive cases among suspected patients demands early careful investigation and management. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i1.26 Chatt Maa Shi Hosp Med Coll J 2013; 12(1): 38-40